The comparison of the efficiency of methotrexate and sulphasalazine treatments in patients with rheumatoid arthritis - Kavuncu, Vural; Şahin, Sezai; Kamanli, Ayhan; Ardiço?lu, Özge (My University, 2002)
The objective of this study is to evaluate the efficacy of sulphasalazine and methotrexate treatment in rheumatoid arthritis (RA). In this prospective study, 15 male and 29 female patients with rheumatoid arthritis were scheduled for sulphasalazine (SSZ) (n=25) or methotrexate (MTX) (n=19) treatment and followed-up for 8 months. Stoke index, which is an algorithm consisting from individual results of proximal interphalngeal joint (PIP) score, erithrocyte sedimentation rate (ESR), duration of morning stiffness, quantitative measurement of CRP concentration and Ritchie Articular Index was used to score the inflammatory activity and Health Assessment Questionnaire (HAQ) was used to assess the disability. In all of the patients, Stoke values were improved in the 4 th month of the therapy, however, this improvement was sustained only in MTX receiving patients in the 8 th month and the decrease in HAQ scores were statistically significant only for the MTX group. In conclusion, the efficacy of MTX in RA treatment is found to be superior to SSZ at eight months. Copyright © 2005 the American Physiological Society.
Keywords: Methotrexate; Rheumatoid arthritis; Sulphasalazine